Persepsi Pengguna Layanan Sistem E-Procurement Pengadaan Barang dan Jasa Pada PT. Sapta Sari Tama - Muhammad Alde Rizal; Ifa Saidatuningtyas; Vutikha Cahya Melati (Politeknik ATI Padang, 2022)
The COVID-19 pandemic has caused the demand for health goods and services to increase. Medicine is one of the important components in the success of the implementation of health efforts. This study aims to evaluate the implementation of electronic procurement of goods and services at PT Sapta Sari Tama, a drug distributor. The results of this study are useful for evaluating the implementation of electronic procurement (E-Procurement) and the basis for developing the E-Procurement system there. This research uses validity test to determine valid variables, reliability test (alpha coefficient) to assess the consistency of answers from sources. Descriptive statistics are used to see the distribution of respondents' answers. The results showed that development can be done on the X5 variable which describes the informativeness of the E-procurement system used.